Review of the genus Thrips and related genera (Thysanoptera, Thripidae) from Japan - Masumoto, Masami; Okajima, Shûji (Zootaxa, 2013)
Members of Thrips genus-group from Japan are reviewed, and 45 species in seven genera are recognized. Nine species and one genus are newly described: Stenchaetothrips amamiensis sp. n., S. dentatus sp. n., S. pleioblasti sp. n., Thrips nonakai sp. n., T. ogasawarensis sp. n., T. shiranesanus sp. n., T. syringae sp. n., T. typicus sp. n. and Tsutsumiothrips ryukyuensis gen. et sp. n. Moreover, 14 species of two genera are newly recorded from Japan: S. langkawiensis Ng & Mound, S. undatus Wang, Thrips alni Uzel, T. aspinus Mound & Masumoto, T. brevicornis Priesner, T. brunneus Ishida, T. extensicornis Priesner, T. minutissimus Linnaeus, T. pini (Uzel), T. subnudula (Karny), T. sukki Bhatti & Lee, T. treher-nei Priesner, T. urticae Fabricius and T. vitticornis Karny. A previously recorded species, Stenchaetothrips bambusae (Shumsher) is excluded from the Japanese fauna.